PERSEPSI CALON GURU MADRASAH IBTIDAIYAH TERHADAP PEMBELAJARAN IPA PADA KURIKULUM DEEP LEARNING - Latifanisa; Anita Ekantini; Ibnu Awall Uddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the perceptions of prospective elementary school teachers towards science learning in a deep learning-based curriculum. The study used a qualitative approach with a descriptive research type. The research subjects were 20 students of the Elementary School Teacher Education Study Program (PGMI) selected using a purposive sampling technique. Data collection techniques were carried out through open-ended questionnaires and interviews. The data obtained were analyzed through the stages of data reduction, categorization, data presentation, and drawing conclusions. The results showed that prospective teachers had a positive perception towards the application of deep learning in science learning. This approach is understood not only to emphasize memorization, but also a deep understanding of concepts through practical activities, observation, discussion, and problem solving. Deep learning-based learning is considered capable of improving students' critical thinking skills, activeness, and learning motivation because the material is linked to everyday life. In addition, the role of the teacher in this approach changes to a facilitator who guides and creates an interactive learning atmosphere. The application of the three main components of deep learning, namely mindful learning, meaningful learning, and joyful learning, is also considered capable of creating more focused, meaningful, and enjoyable learning. Thus, the deep learning approach is considered relevant to support science learning in the Independent Curriculum.